PEDAGOGICAL COMMUNICATION STYLES AND FUNCTIONS (Web of Teachers: Inderscience Research, 2024)
This article provides information about the methods and functions of pedagogical communication, the influence of pedagogical communication, as well as the importance of pedagogical communication in the process of communicating with young people.